The impact of letter detection on eye movement patterns during reading: Reconsidering lexical analysis in connected text as a function of task - Greenberg, Seth N. (2006)
A comparison was made between reading tasks performed with and without the additional requirement of detecting target letters. At issue was whether eye movement measures are affected by the additional requirement of detection. Global comparisons showed robust effects of task type with longer fixations and fewer word skippings when letter detection was required. Detailed analyses of target words, however, further showed that reading with and without letter detection yielded virtually identical effects of word class and text predictability for word-skipping rate and similar effects for different word viewing duration measures. The overall oculomotor pattern suggested that detection does not substantially shift normal reading movements in response to lexical cues and thereby indicated that detection tasks are informative about word and specifically word class processing in normal reading.